Ratatouille Ratatuy - Bird, Brad (United States : Buena Vista Pictures, 2007)
A rat named Remy dreams of becoming a great French chef despite his family's wishes and the obvious problem of being a rat in a decidedly rodent-phobic profession. When fate places Remy in the sewers of Paris, he finds himself ideally situated beneath a restaurant made famous by his culinary hero, Auguste Gusteau. Despite the apparent dangers of being an unlikely - and certainly unwanted - visitor in the kitchen of a fine French restaurant, Remy's passion for cooking soon sets into motion a hilarious and exciting rat race that turns the culinary world of Paris upside down.
Languages : Turkish, English.
Region 2.
Subtitles : Turkish, English.
Cast: Patton Oswalt, Ian Holm, Lou Romano, Brian Dennehy, Peter Sohn.
K-3.
Keywords: Movie -- animated films